Functional moments estimators analysis by the Monte-Carlo method for model of mixture with varying concentrations - Oksana, Kubaychuk (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
The functional moments estimation by the sample from the mixture with varying concentrations is studied. The problem of efficiency the simple linear estimator with fixed weight against the adaptive or improved estimators with random weight is considered. By the Monte-Carlo method it is shown that simple linear estimator is better for small sample sizes, but for large samples the adaptive and improved estimators are more efficient.